Vocational High School Of Nursing Major Needs Analysis Of English For Specific Purposes (Esp): A Case Study In Purwakarta: English - Reiza Farha Aini Ratu; Yogi Setia Samsi (Journal of English Development, 2023)
English for Specific Purposes ESP focuses on teaching English to students for a specific purpose. English for Specific Purposes can be used to help students gain the language skills they need to succeed in their chosen field. English is an essential skill for students in vocational schools. This study will focus on English for nursing students. It aims to identify the learning needs of students in vocational schools. This search would be better if respondents were added to make it larger or include all students in the school. For example, poll all students to get more relevant data. The questions are also more specific to see how the learning is going. The study should also use multiple previous studies to analyze existing data more accurately. Questionnaire questions should also be more specific so that you can see what difficulties students have, what form of learning they prefer, what skills students prefer in learning English, and opinions. their English.